2015
DOI: 10.4103/2249-4863.161339
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of morbidity pattern, quality of life and awareness of government facilities among elderly population in South India

Abstract: Background:This study was done to assess the determinants of morbidity pattern, quality of life (QoL) and awareness of elderly about various government schemes and social security legislations.Materials and Methods:Data was collected by house to house survey among participants aged 60 years and above using a structured interview schedule. The QoL was assessed using Kannada version of WHOQOL-BREF instrument following language validation.Results:Mean age of 206 participants was 69.6±6.7 years. Half of them were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
10
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
6
10
2
Order By: Relevance
“…[17][18][19] The prevalence of hypertension in our study was 49% which is similar to the findings of Hameed et al in Karnataka and Joseph et al in South India. 10,15 The prevalence of cataract in our study was 30% which is comparable to the study findings of Sharma et al 12 Few studies however have reported lower prevalence of morbidities as compared to our study. A study conducted in southern rural area of Pondicherry by Sudarshan et al, found that hypertension was prevalent in 14.2% subjects, arthritis in 12.3% subjects and similarly magnitude of other morbidities was quite low.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…[17][18][19] The prevalence of hypertension in our study was 49% which is similar to the findings of Hameed et al in Karnataka and Joseph et al in South India. 10,15 The prevalence of cataract in our study was 30% which is comparable to the study findings of Sharma et al 12 Few studies however have reported lower prevalence of morbidities as compared to our study. A study conducted in southern rural area of Pondicherry by Sudarshan et al, found that hypertension was prevalent in 14.2% subjects, arthritis in 12.3% subjects and similarly magnitude of other morbidities was quite low.…”
Section: Discussionsupporting
confidence: 89%
“…[12][13][14] The mean number of morbidities in our study was 2.72±1.72 which is comparable to the study findings of Jospeh et al who reported a mean of 2.4±1.2 in southern India. 15 Our study reported that musculoskeletal disorders were the most prevalent morbidity among elderly with a prevalence of 57.3%. A study conducted in Shimla hills by Sharma et al also reported a similar finding that musculoskeletal problems were the most prevalent morbidity (56.5%).…”
Section: Discussionmentioning
confidence: 70%
“…18 In our present study, the sociodemographic dominance of predominant Muslim population in the study area (52.5%) coupled with only literates (55.8%) and enough population belonging to backward castes (SC/ST ± OBC, 21.6%) explains the significant presence of morbid conditions in our study area just similar to other studies. [8][9][10][11]18,19 Our study findings also corroborate with other studies in the literature, [24][25][26] which however suggests that although PHC is the best approach to achieving universal health coverage 24,25 and a fundamental requirement for achieving the Sustainable Development Goals, 22,24 its real positive impact on health status is questionable. Unfortunately, the concept of PHC was created at AlmaAta in 1978, and many countries have failed to establish effective PHC.…”
supporting
confidence: 82%
“…7 It has been evident from the literature that many factors influence morbidity patterns in rural areas as catered by a health center or hospital, such as demographic, social, household, and economic. [8][9][10][11] Studies conducted in different states of India 12-17 also indicate that the case rate is higher not only for the 18 to 45 years age group but also for preschool children, adolescents, and the elderly in rural areas. 18 Moreover, it has been seen that factors, such as cleanliness of the premises, face-lift, and clean toilet with privacy and availability of safe drinking water facilities can improve client satisfaction in rural health care delivery systems.…”
Section: 2mentioning
confidence: 99%
“…This is lower than figures reported by Joseph N et al, in their study conducted in Mangalore city. The possible reasons could be higher literacy rate of subjects in that study and rural urban differentials [8].…”
Section: Subjects Below Poverty Linementioning
confidence: 99%